Incident Cardiovascular Risk Factors Among Men and Women Veterans After Return From Deployment. Issue 11 (November 2017) - Haskell, Sally G.; Brandt, Cynthia; Burg, Matthew; Bastian, Lori; Driscoll, Mary; Goulet, Joseph; Mattocks, Kristin; Dziura, James
Abstract : Background: Stressors associated with military service and reintegration may impact psychologic well-being and behaviors that result in increased incidence rates for cardiovascular (CV) risk factors. Objective: Using electronic health record data from the Veterans Health Administration we sought to measure the incidence of newly diagnosed CV risk factors and how these incident risks were moderated by race and mental health conditions. Design: A cohort study including Veterans whose end of last deployment was between October 1, 2001 and July 31, 2014. Subjects: A total of 267, 305 Operations Iraqi Freedom, Enduring Freedom, and New Dawn Veterans were present. Main Outcome Measures: Incident risk factors (hypertension, obesity, dyslipidemia, diabetes, or coronary artery disease), identified through new International Classification of Diseases, 9th Revision, Clinical Modification diagnostic codes or measurement recordings at primary care visits. Results: The rate of developing at least 1 risk factor or coronary artery disease was 240 and 151 per 1000 person-years in men and women, respectively. Except for obesity, women were significantly less likely to develop any other CV risk factor compared with men (Crude hazard ratios ranging from 0.44 to 0.82). The impact of sex on hypertension ( P <0.001) and obesity ( P <0.001) was modified by race and the impact of sex on the combined event of any risk factor ( P =0.007) and obesity ( P <0.001) was modified by depression. Conclusions: Compared with men, women Veterans were more likely to become obese after return from deployment, but less likely to develop any other risk . For black women, the protective effect of female sex on the combined event (any risk factor), and hypertension was lessened compared with white women. The increased risk of obesity for women was greater in black women, and those with depression. Abstract : Supplemental Digital Content is available in the text.